The Global Rise of Diabetes – Time to Think Seriously About Environmental Toxicants as Risk Factors for Development of the Disease - George B. Kudolo (Pancreas, 2022)
It is now estimated that the number of people living with diabetes worldwide in 2045 will be approximately 783 million, rising much faster than the global population growth of about 20%. In addition to the traditional known host risk factors (life-style changes associated with urbanization, physical inactivity, obesity and aging), it is probably prudent to begin to give serious thought to exposure to environmental toxicants, either because of mere geographical location or because of human industrial activity, as possible significant contributors. This knowledge could raise awareness while prompting us to find new ways to protect people and the environment.